Aldosterone promotes vascular remodeling by direct effects on smooth muscle cell mineralocorticoid receptors - Pruthi, Dafina (2013)
OBJECTIVE: Vascular remodeling occurs after endothelial injury resulting in smooth muscle cell (SMC) proliferation and vascular fibrosis. We previously demonstrated that the blood pressure-regulating hormone aldosterone enhances vascular remodeling in mice at sites of endothelial injury in a placental growth factor (PlGF)-dependent manner. We now test the hypothesis that SMC mineralocorticoid receptors (MR) directly mediate the remodeling effects of aldosterone and further explore the mechanism. APPROACH AND RESULTS: A wire-induced carotid injury model was performed in wild type (WT) mice and mice with inducible SMC-specific deletion of MR (SMC-MR-KO). Aldosterone did not affect re-endothelialization after injury in WT mice. Deletion of SMC-MR prevented the 79% increase in SMC proliferation induced by aldosterone after injury in MR-Intact littermates. Moreover, both injury-induced and aldosterone-enhanced vascular fibrosis were attenuated in SMC-MR-KO mice. Further exploration of the mechanism revealed that aldosterone-induced vascular remodeling is prevented by blockade of the PlGF-specific receptor, VEGFR1, in vivo. Immunohistochemistry of carotid vessels shows that the induction of VEGFR1 expression in SMC after vascular injury is attenuated by 72% in SMC-MR-KO mice. Moreover, aldosterone induction of vascular PlGF mRNA expression and protein release are also prevented in vessels lacking SMC-MR. CONCLUSIONS: These studies reveal that SMC-MR is necessary for aldosterone-induced vascular remodeling independent of renal effects on blood pressure. SMC-MR contributes to induction of SMC VEGFR1 in the area of vascular injury and to aldosterone-enhanced vascular PlGF expression and hence the detrimental effects of aldosterone are prevented by VEGFR1-blockade. This study supports exploring MR antagonists and VEGFR1-blockade to prevent pathological vascular remodeling induced by aldosterone.